Error Analysis and Distribution of 6-SPS and 6-PSS Reconfigurable Parallel Manipulators - 姚蕊 唐晓强 李铁民 林春深 (Tsinghua science and technology, 2010)
The purpose of this paper is to analyze an accuracy design method for reconfigurable parallel manipulators including a 6-SPS and a 6-PSS parallel manipulator.An error analysis method,based on the module error model,was used to express the relationship between the module error and the terminal error in the error transmission equation of the reconfigurable parallel manipulator.In addition,an error distribution method using a manufacturing and assembly difficulty coefficient was used to analyze each error module to determine a maximum terminal error.The error distribution result was then used to set up a reconfigurable parallel manipulator.Error experiments with a reconfigurable parallel manipulator show that the error analysis and distribution method for reconfigurable parallel manipulators are effective and the maximum terminal errors of the reconfigurable parallel manipulators are less than 50 μm.